Monte Carlo Simulation of Atomic Diffusion: Gold into Silicon - P, Poovanaesvaran; Abdul Jalil, Ithnin (Malaysian Journal of Science, 2006)
iffusion by vacancy mechanism, interstitial mechanism, kick-out mechanism and Frank-Turnbull mechanism in crystalline solids are analyzed through Monte Carlo simulation. These diffusion mechanisms are strongly dependent on the temperature. The simulation was done to find the dominant diffusion mechanism of Au into Si for temperatures ranging from 500K to 1800K. The result shows that the vacancy mechanism is the dominant diffusion, followed by kick-out, interstitial and Frank-Turnbull. Kick-out mechanism only appears at 670 K, interstitial at 850 K and Frank-Turnbull at 1500 K.